The Mediation Role of Financial Performance on the Influence of Green Accounting on Banking Sector Company Value - Trisnabudi, Ardian Noor; Isnalita (Yayasan Sinergi Kawula Muda, 2025)
This study aims to examine the influence of green accounting and financial performance on company value and the role of economic performance in mediating the impact of green accounting on company value. The research population is 47 banking companies listed on the IDX from 2021 to 2023. The sampling technique used purposive sampling with 132 observation research samples. The results of the study show that green accounting has a positive effect on company value. At the same time, financial performance cannot mediate the influence of green accounting on company value. The study's results support the stakeholder theory that companies must consider environmental impacts to improve relationships with other stakeholders. The research results can also encourage governments and regulatory authorities to develop policies that support ecological transparency and sustainable accounting reporting. This research is limited to collecting green accounting data for some companies that do not present sustainability reports separately, making it difficult for researchers to trace the data.